Activation of complement C1q and C3 in glomeruli might accelerate the progression of diabetic nephropathy: Evidence from transcriptomic data and renal histopathology. Issue 5 (10th January 2022) - Jiao, Yuanyuan; Jiang, Shimin; Wang, Ying; Yu, Tianyu; Zou, Guming; Zhuo, Li; Li, Wenge
ABSTRACT: Aims/Introduction: It is not unclear whether the complement system is involved in the pathogenesis of diabetic nephropathy (DN). We explored the role of the complement system in glomeruli from patients with DN using integrated transcriptomic bioinformatics analysis and renal histopathology. Materials and Methods: Four datasets (GSE30528, GSE104948, GSE96804 and GSE99339) from the Gene Expression Omnibus database were integrated. We used a protein–protein interaction network and the Molecular Complex Detection App to obtain hub genes. Gene ontology and the Kyoto Encyclopedia of Genes and Genomes pathway enrichment analyses were carried out to identify significant pathways. We also investigated the associations of C1q and C3 deposition on renal histopathology with clinical data, pathological parameters and renal survival in DN patients. Results: We identified 47 up‐ and 48 downregulated genes associated with DN. C3, C1QB and C1QA were found to be complement‐related hub genes. The gene ontology and Kyoto Encyclopedia of Genes and Genomes analyses identified complement activation and humoral immune response as the significant oncology terms, with C1QB and C3 positioned at the center of the pathway. Regarding renal histopathology, patients with both C1q and C3 deposition had more severe glomerular classes. Multivariate Cox proportional hazards regression showed that the deposition of glomerular C1q and C3 was an independent risk factor for kidney failure. Patients with high C1q, C3 or C4d expression in glomeruli were more likely to progress to kidney failure, whereas glomerular mannose‐binding lectin was rare. Conclusions: Complement activation is involved in the development of DN, and activation of the classical complement pathway in glomeruli might accelerate disease progression. Abstract : Local complement activation is involved in the development of diabetic nephropathy and deposition of complement C1q and C3 in glomeruli may accelerate the progression of diabetic nephropathy. New approaches to modulate the complement system might lead to the development of new agents to prevent or slow the progression of diabetic nephropathy.